The Quality of Environmental Data Disclosure. The case of Public Companies from the European Union Countries - Janicka, Małgorzata; Sajnóg, Artur (European Journal of Sustainable Development, 2023)
In the 21st century business entities are required to change priorities and move to a sustainable relationship between environmental, social, and economic well-being. Climate and environment are phenomena of transnational and global nature, and for this reason, actions in this area should be taken at a supranational level. Nowadays, the European Union (EU) countries have been implementing directives concerning environmental changes and taxonomy for non-financial reporting. According to their requirements, public companies must disclose high-quality data in the ESG area, including the environmental indicator (E) and its components. The purpose of the study is to discuss the current state of disclosure of environmental data by public companies listed on the regulated markets of the European Union. Special emphasis is devoted to energy consumption, water, waste production, and CO2 emissions. To test the quality of environmental indicators, we used the Refinitiv database. The research period covers 2012–2021. The research sample consists of public companies listed on the leading stock markets in 27 EU member states. The findings support the clear advantage of the quality of environmental data disclosure in the ‘old’ EU member states (which joined before 2004) as to compared to the ‘new’ EU member states. Keywords: environmental disclosure, environmental reporting, ESG, European Union, public companies.